2010
DOI: 10.1002/chem.200903516
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Recoverable Core–Shell Nanocomposites with Enhanced Photocatalytic Activity

Abstract: Core–shell structured Fe3O4/SiO2/TiO2 nanocomposites with enhanced photocatalytic activity that are capable of fast magnetic separation have been successfully synthesized by combining two steps of a sol–gel process with calcination. The as‐obtained core–shell structure is composed of a central magnetite core with a strong response to external fields, an interlayer of SiO2, and an outer layer of TiO2 nanocrystals with a tunable average size. The convenient control over the size and crystallinity of the TiO2 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
207
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(212 citation statements)
references
References 39 publications
5
207
0
Order By: Relevance
“…Xue et al found that the presence of silica layer between Fe 3 O 4 and TiO 2 nanoparticles could increase the lifetime of hole (h + ) product and yield a better photoreactivity 10 . The magnetic photocatalyst material has been applied for degradation of organic pollutants [11][12][13][14] . In this contribution, we report on the magnetic photocatalyst of Fe 3 O 4 /SiO 2 /TiO 2 core-shell for silver ion photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al found that the presence of silica layer between Fe 3 O 4 and TiO 2 nanoparticles could increase the lifetime of hole (h + ) product and yield a better photoreactivity 10 . The magnetic photocatalyst material has been applied for degradation of organic pollutants [11][12][13][14] . In this contribution, we report on the magnetic photocatalyst of Fe 3 O 4 /SiO 2 /TiO 2 core-shell for silver ion photoreduction.…”
Section: Introductionmentioning
confidence: 99%
“…1D). It should be noted that the To explore the role of MgSO 4 in the coating process, the CS@SBA-15 100H sample is synthesized without addition of MgSO 4 . It is found that the CS@SBA-15 100H sample still possesses the spherical morphology with the diameter about 900 nm, indicating the mesoporous silica coated on the surface of carbon spheres (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] At present, core-shell materials with differnet shell compositions such as polymer, carbon, mental, silica and mesoporous silica have been successfully synthesized. [5][6][7][8][9] Regarding the diverse kinds of core-shell structures, mesoporous silica coated inorganic nanomaterials have attracted great attention in reacent years because the mesoporous silica shells can serve as beginning isolated interface and easily modifiable surface, and also provide with high surface area, volume and proper accessible pore channels.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] A relatively favorable condition of self-propagating combustion method owns simple operation, high reaction efficiency, a lower cost and simple equipment, but a forward reaction speed, inhomogeneous and easycongregative samples. The combination technique with sol-gel and self-propagating combustion coupled method organically bands the two methods together, overcome each other's shortcomings and exploit the advantages, and the technique has gradually become a recent focus to prepare metal oxide or metal compound oxide at home and abroad in nearly 30 years.…”
Section: General Instructionsmentioning
confidence: 99%
“…Some element valencies were counted according to the rule, resulting as the valency of carbon element +4, hydrogen +1, oxygen -2, cerium +3 and nitrogen 0. Then, the valency of oxidizer nitric acid cerium Ce(NO 3 ) 3 . 6H 2 O was described as: +3+3×(0-3×2)+ 6×(1×2-2) = -15, similarly, reducer stearic acid C 18 H 36 O 2 displayed +104.…”
Section: Theoretical Calculating Data Of Stearic Acid Dosage By the Pmentioning
confidence: 99%